Using Framing Theory to Facilitate the Influence of Collaborative Learning on Teacher Noticing: A Case of Chinese Lesson Study - Zuo (左思宇), Siyu; Qi (綦春霞), Chunxia (ECNU Review of Education, 2025)
Purpose This study investigates how collaborative, lesson study-style professional development improves teacher noticing behaviors in the context of unit-based mathematics teaching in China. We employed framing theory to understand the phenomenon. First, the study aims to reveal the change in teacher noticing and frames before and after professional development; second, it seeks to clarify the influence of cultural factors in these changes. Design/Approach/Methods Questionnaires were used to collect data on 10 teacher noticing skills and semi-structured interviews were used to explore their views of the factors influencing change. These data were analyzed thematically to identify noticing behaviors, infer frames, and identify sociocultural influences; the Wilcoxon signed-rank test was used to reveal changes in noticing behaviors. Findings First, teachers demonstrated varying degrees of improvement in three sub-skills of noticing and five teachers demonstrated a shift in framing. Second, the cultural factors influencing these shifts were summarized. Originality/Value This study enriches the literature on teacher noticing and frames by providing a detailed analysis of a lesson study, and it contributes to the theories of teacher noticing and framing.